Accountants’ Perceptions on the Adoption of International Financial Reporting Standards in Yemen - Al-Absy, Mujeeb Saif Mohsen; Ku Ismail, Ku Nor Izah; Al-Dubai, Shehabaddin Abdullah A. (International Journal of Economics and Financial Issues, 2016)
Developments in the global capital market have made the adoption of International Financial Reporting Standard (IFRSs) more significant than ever before. The purpose of this study is to examine the accountants’ perception of IFRSs adoption in Yemen. We also seek the accountants’ view on whether Yemen should adopt the IFRSs or not, and on the expected time taken to adopt the accounting standards. We also examine the difference in opinion between academicians and practitioners regarding the adoption of IFRSs. In this regard, this study carries out a survey of 48 Yemeni accounting postgraduate students in Malaysian public universities. We find that a majority of the respondents acknowledge the benefits of adopting IFRSs in Yemeni companies. Moreover, a majority of the respondents (82.9%) agree that Yemeni companies should adopt IFRSs. About 58.6% of respondents expect the period of IFRSs adoption in Yemen to be within three to 10 years, while 41.5% expect it to be more than 10 years. The results of this study may help policy-makers and the Yemeni Association of Certified Public Accountants (YACPA) make more precise decisions regarding IFRSs adoption in Yemen. Keywords: IFRSs, accounting standard convergence, Yemen JEL Classifications: M4, M48